Talking to the Eyes by Drawing: Design Representations in the Magazines in the Mid-19th-Century (diségno, 2018)
Since the 1840s in Germany, England and France, the architectural magazines, born in the last years of the 18th-century, have been considered a privileged medium for the spread of architectural debate and topicality. Driven by continuous improvements in printing techniques, design representations have increased and been integrated with texts in ever more organic ways, reflecting the need for an ambit in which the respective professional skills are defined. New architectural typologies, materials and construction techniques are shared through drawings that, in the different geographical areas, take on particular features, which are linked to artistic culture, architectural debate and the representation methods developed in the Enlightenment schools and proposed in the coeval treatises.
Keywords: Design drawing; Architecture magazines; Representation methods; Representation techniques